Staff Operational Guidelines on Dissemination of Technical Assistance Information. (Policy Papers; Policy Paper ;, 2013)
TA information should be disseminated more widely. The more active sharing of TA information with donors and other TA providers will improve coordination, exploit synergies, and enable the IMF to prioritize and leverage its limited TA resources, thereby fulfilling key objectives under the Paris Declaration on Aid Effectiveness. Moreover, especially from the perspective of their own accountability to their governments and legislators, donors to the IMF's TA program have a legitimate interest in receiving information on TA that is financed by them. For TA recipient countries, the wider dissemination of TA information among different government agencies will strengthen ownership and facilitate the more effective implementation of TA recommendations. More generally, through publication, the membership and the public at large will benefit from a better understanding of best practices, and the IMF's experiences in the provision of TA.